Molecular interactions between two lmp2a py motifs of ebv and ww domains of e3 ubiquitin ligase aip4 - Seo, Min Duk; Seok, Seung Hyeon; Kim, Ji Hun; Choi, Ji Woong; Park, Sung Jean; Lee, Bong Jin (Life, 2021)
Interactions involving Epstein–Barr virus (EBV) LMP2A and Nedd4 family E3 ubiquitin– protein ligases promote the ubiquitination of LMP2A-associated proteins, which results in the perturbation of normal B-cell signaling. Here, we solved the solution structure of the WW2 domain of hAIP4 and investigated the binding mode involving the N-terminal domain of LMP2A and the WW2 domain. The WW2 domain presented a conserved WW domain scaffold with a three-stranded anti-parallel β-sheet and bound two PY motifs via different binding mechanisms. Our NMR titration and ITC data demonstrated that the PY motifs of LMP2A can recognize and interact weakly with the XP groove of the WW2 domain (residues located around the third β-strand), and then residues between two PY motifs optimize the binding by interacting with the loop 1 region of the WW2 domain. In particular, the residue Val15 in the hairpin loop region between β1 and β2 of the WW2 domain exhibited unique changes depending on the terminal residues of the PY motif. This result suggested that the hairpin loop is responsible for additional interactions outside the XP groove, and this hypothesis was confirmed in a deuterium exchange experiment. These weak but wide interactions can stabilize the complex formed between the PY and WW domains.
Keywords: AIP4; E3 ubiquitin ligase; EBV; LMP2A; NMR